Burden of HIV among female sex workers in low-income and middle-income countries: a systematic review and meta-analysis. - Baral, Stefan; Beyrer, Chris; Muessig, Kathryn; Poteat, Tonia; Wirtz, Andrea L; Decker, Michele R; Sherman, Susan G; Kerrigan, Deanna (The Lancet infectious diseases, 2012)
Female sex workers are a population who are at heightened risk of HIV infection secondary to biological, behavioural, and structural risk factors. However, three decades into the HIV pandemic, understanding of the burden of HIV among these women remains limited. We aimed to assess the burden of HIV in this population compared with that of other women of reproductive age.
Keywords: Africa; Asia; Developing Countries; Europe, Eastern; Female; HIV Infections; Humans; Latin America; Prevalence; Sex Workers